2016
DOI: 10.2147/imcrj.s116771
|View full text |Cite|
|
Sign up to set email alerts
|

Retropupillary iris claw intraocular lens implantation in aphakia for dislocated intraocular lens

Abstract: BackgroundNowadays, dislocated intraocular lenses (IOLs) and inadequate capsular support are becoming a challenge for every ophthalmic surgeon. Explantation of dislocated IOL and iris claw IOL (ICIOL) are the techniques that have been used in our ophthalmic department. The aim of this study is to report our technique for retropupillar ICIOL.MethodsThis study is a retrospective case series. A total of 105 eyes with dislocated IOL from the patients at the Department of Ophthalmology in Santa Maria Hospital, a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(57 citation statements)
references
References 23 publications
1
56
0
Order By: Relevance
“…Reported complications of ICIOL implantation include endothelial cell loss, corneal decompensation, pigment dispersion, hyphema, transient IOP elevation, secondary glaucoma, IOL dislocation, pupillary block, anterior uveitis, cystoid macular edema, hypotonia, choroidal detachment, retinal detachment, and vitreous hemorrhage. 6,7,10,11,12,13,14,15,16,17,18,19,20,21,22,23 None of the patients in this study showed pigment dispersion, uveitis, cystoid macular edema, hypotonia, choroidal detachment, retinal detachment, or vitreous hemorrhage within the first postoperative year, while other complications occurred at rates considered acceptable in terms of safety, as stated in the literature.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Reported complications of ICIOL implantation include endothelial cell loss, corneal decompensation, pigment dispersion, hyphema, transient IOP elevation, secondary glaucoma, IOL dislocation, pupillary block, anterior uveitis, cystoid macular edema, hypotonia, choroidal detachment, retinal detachment, and vitreous hemorrhage. 6,7,10,11,12,13,14,15,16,17,18,19,20,21,22,23 None of the patients in this study showed pigment dispersion, uveitis, cystoid macular edema, hypotonia, choroidal detachment, retinal detachment, or vitreous hemorrhage within the first postoperative year, while other complications occurred at rates considered acceptable in terms of safety, as stated in the literature.…”
Section: Discussionsupporting
confidence: 62%
“…Although ICIOL implantation in aphakic eyes is easier and safer than other methods, complication rates vary widely between publications. 6,7,10,11,12,13,14,15,16,17,18,19,20,21,22,23 These differences may result from variation in surgical histories, placement of the ICIOL in the anterior chamber or retropupillary space, and surgeon experience. Reported complications of ICIOL implantation include endothelial cell loss, corneal decompensation, pigment dispersion, hyphema, transient IOP elevation, secondary glaucoma, IOL dislocation, pupillary block, anterior uveitis, cystoid macular edema, hypotonia, choroidal detachment, retinal detachment, and vitreous hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 3 ] In addition, sclerally fixated IOLs also have some drawbacks such as retinal detachment, IOL decentration, conjunctival erosion, and endophthalmitis. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%